Land Suitability Evaluation for Pigeon Pea in Semi-arid Land, South Telangana Plateau, India, Using GIS, Remote Sensing and Detailed Survey. Issue 6 (26th March 2022) - M, Chandrakala; Srinivasan, R.; Prasad, Bhoora; K.V, Niranjana; K, Sujatha; Hegde, Rajendra; Chandran, P.; Dwivedi, B.S.; Maske, Sunil P.
ABSTRACT: Soil-crop suitability evaluation is a prerequisite to achieve elevated production and productivity per unit land, cost, inputs, and manpower. In order to identify potential crop land for pigeon pea ( Cajanus cajan L. Mill sp.) cultivation in South Telangana Plateau (Rayalseema), a case study was taken at Rayachoty mandal (23240.7 ha), Yeduguri Sandinti Rajasekhara Reddy (YSR) Kadapa district, Andhra Pradesh. A detailed soil survey at 1:10000 scale was carried out to inventory land resources using sentinel-2 satellite imagery and toposheet as base. Based on physical, chemical, and morphological properties, 10 soil series and 53 mapping units were identified. Among 53 mapping units, 5 mapping units (6.61%) are moderately suitable (Class S1), 40 mapping units (57.48%) are marginally suitable (Class S3) and 8.07% of total area is unsuitable for pigeon pea cultivation. The major limitations were topography, soil texture, gravelliness, soil fertility, root restriction and drainage. The study has implications on increasing the area under pigeon pea cultivation by addressing the limitations in specific mapping units in semi-arid land of south Telangana plateau by adopting suitable soil and water conservation measures for elevated pigeon pea production and productivity.